Arteriolosclerosis of the human renal allograft: morphology, origin, life history and relationship to cyclosporine therapy - Rossmann, P; Jirka, J; Chadimová, M; Reneltová, I; Saudek, F (Virchows Archiv. A, Pathological anatomy and histopathology, 1991)
In the decade 1979-1988, 658 biopsies were collected from 568 cadaveric renal allografts. In 118 grafts a non-proliferative insudative vasculopathy (IVA) was found in afferent vessels. Immunosuppression was based on azathioprine (AZA) or on cyclosporin A (CsA), from 1983. The prevalence and extent of IVA has increased significantly since 1984. Light microscopy showed fibrinoid and hyaline masses of varying extent; transmural insudative "knobs", intimal oedema with metachromasia, and microthrombosis were also seen with CsA. The ultrastructure of the insudates was unremarkable but CsA grafts displayed early oedema and hypergranulation of endothelial cells with a disarray of smooth muscle cell (SMC) microfibrils, and pronounced degenerative changes of SMC. Rebiopsy showed stationary IVA in AZA grafts and progression in one-half of CsA-treated patients. Nephrectomy specimens revealed, however, a marked predominance of late rejection endarteritis; in only 3 cases was IVA and/or microthrombosis the possible cause of nephrectomy. The mean donor age was higher in severe IVA in CsA grafts and the mean post-transplantation interval at the time of diagnosis of IVA was significantly shorter in CsA-treated patients. No important differences in cumulative graft survival were seen between grafts with absent, moderate or severe IVA. Unused cadaveric donors' kidneys of comparable age exhibited normal arterioles or a slight focal insudative or hyaline lesion.
Keywords: fluorescenční protilátková technika; Humans; Microscopy, Electron; prevalence; ledviny; Graft Rejection; Kidney; lidé; arterioskleróza; cyklosporiny; imunosupresivní léčba; Transplantation, Homologous; arterie; transplantace ledvin; Arteries; arterioly; Immunosuppression Therapy; Kidney Transplantation; Arterioles; Prevalence; Fluorescent Antibody Technique; elektronová mikroskopie; homologní transplantace; rejekce štěpu; Cyclosporins; Arteriosclerosis